MANAGEMENT OF BREAST FEEDING IN DEPARTMENTS FOR PRETERM INFANTS - L. V. Abol'yan; S. A. Polyanskaya; S. V. Novikova; A. V. Deryu ("Paediatrician" Publishers LLC, 2014)
Progress of the modern medicine science and rapid development of perinatal technologies allow bringing up severely preterm infants with very low and extremely low birth weight. The significance of appropriate nutritive support for the preterm infants at the early stages of postnatal life is very high and to a great extent determines prognosis of their further development and survival. Taking into account a special biological value of the breast milk for preterm infants and an important role of the mother's contact with her child during feeding, the efforts of the medical staff should be aimed at the maintaining of the breast feeding to the maximal extent. Introduction of the modern medical technologies of protection and support of the breast feeding into the practice of medical institutions allows increasing the prevalence of the breast feeding among the preterm infants. However despite the certain achievements in the field of modern management technologies aimed at the support of the breast feeding, the further investigations on adaptation of the principles of successful breast feeding under conditions of departments for preterm infants are demanded.